Critical care nurses' clinical reasoning about physiologic monitor alarm customisation: An interpretive descriptive study. Issue 15 (22nd April 2019) - Ruppel, Halley; Funk, Marjorie; Whittemore, Robin; Wung, Shu‐Fen; Bonafide, Christopher P.; Powell Kennedy, Holly
Abstract: Aims and objectives: To explore clinical reasoning about alarm customisation among nurses in intensive care units. Background: Critical care nurses are responsible for detecting and rapidly acting upon changes in patients' clinical condition. Nurses use medical devices including bedside physiologic monitors to assist them in their practice. Customising alarm settings on these devices can help nurses better monitor their patients and reduce the number of clinically irrelevant alarms. As a result, customisation may also help address the problem of alarm fatigue. However, little is known about nurses' clinical reasoning with respect to customising physiologic monitor alarm settings. Design: This article is an in‐depth report of the qualitative arm of a mixed methods study conducted using an interpretive descriptive methodological approach. Methods: Twenty‐seven nurses were purposively sampled from three intensive care units in an academic medical centre. Semi‐structured interviews were conducted by telephone and were analysed using thematic analysis. Consolidated Criteria for Reporting Qualitative Research (COREQ) reporting guidelines were used. Results: Four themes were identified from the interview data: unit alarm culture and context, nurse attributes, motivation to customise and customisation "know‐how." A conceptual model demonstrating the relationship of these themes was developed to portray the factors that affect nurses' customisation of alarms. Conclusions: In addition to drawing on clinical data, nurses customised physiologic monitor alarms based on their level of clinical expertise and comfort. Nurses were influenced by the alarm culture on their clinical unit and colleagues' and patients' responses to alarms, as well as their own technical understanding of the physiologic monitors. Relevance to clinical practice: The results of this study can be used to design strategies to support the application of clinical reasoning to alarm management, which may contribute to more appropriate alarm customisation practices and improvements in safety.